Community‐wide consequences of sexual dimorphism: evidence from nectar microbes in dioecious plants. Issue 11 (14th September 2018) - Tsuji, Kaoru; Fukami, Tadashi
Abstract: Intraspecific trait variation is receiving renewed interest as a factor affecting the structure of multi‐species communities within and across trophic levels. One pervasive form of intraspecific trait variation is sexual dimorphism in animals and plants, which might exert large effects particularly on the communities of host‐associated organisms, but the extent of these effects is not well understood. We investigated whether host‐associated microbial communities developed differently in the floral nectar of female and male individuals of the dioecious shrubs, Eurya emarginata and E. japonica . We found that nectar‐colonizing microbes such as bacteria and fungi were more than twice as prevalent and, overall, more than 10 times as abundant in male flowers as in female flowers. Microbial species composition also differed between flower sexes. To examine potential mechanisms behind these differences, we manipulated the frequency of flower visitation by animals and the order of arrival of microbial species to nectar. Animal visitation frequency affected microbial communities more greatly in male flowers, while arrival order affected them more in female flowers. These sex‐specific effects appeared attributable to differences in how animals and microbes altered the chemical characteristics of nectar that limited microbial growth. Taken together, our results provide evidence that sexual dimorphism can have large effects on the structure of host‐associated communities.